2021
DOI: 10.1101/2021.12.04.471186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term labeling and imaging of synaptically-connected neuronal networksin vivousing double-deletion-mutant rabies viruses

Abstract: SummaryThe highly specific and complex connectivity between neurons is the hallmark of nervous systems, but techniques for identifying, imaging, and manipulating synaptically-connected networks of neurons are limited. Monosynaptic tracing, or the gated replication and spread of a deletion-mutant rabies virus to label neurons directly connected to a targeted population of starting neurons1, is the most widely-used technique for mapping neural circuitry, but the rapid cytotoxicity of first-generation rabies vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 94 publications
(110 reference statements)
3
25
0
Order By: Relevance
“…Beginning one week later, we began imaged the calcium signals in the labeled neurons in a series of imaging sessions that continued until 16 weeks postinjection, in the awake mice viewed visual stimuli consisting of drifting gratings of different orientations and frequencies. Just as we found previously for ∆GL viruses (Chatterjee et al, 2018;Jin et al, 2021b), we found no signs of dysfunction in cells labeled by the thirdgeneration vector for as long as we followed them (Figure 4; see also Figures S4 and S5. See File S4 for all counts and statistical comparisons and Video S2 for an example of calcium responses in a group of cortical neurons 16 weeks after injection of RV∆L-Cre).…”
Section: Longitudinal Functional Two-photon Imaging In Vivosupporting
confidence: 87%
See 4 more Smart Citations
“…Beginning one week later, we began imaged the calcium signals in the labeled neurons in a series of imaging sessions that continued until 16 weeks postinjection, in the awake mice viewed visual stimuli consisting of drifting gratings of different orientations and frequencies. Just as we found previously for ∆GL viruses (Chatterjee et al, 2018;Jin et al, 2021b), we found no signs of dysfunction in cells labeled by the thirdgeneration vector for as long as we followed them (Figure 4; see also Figures S4 and S5. See File S4 for all counts and statistical comparisons and Video S2 for an example of calcium responses in a group of cortical neurons 16 weeks after injection of RV∆L-Cre).…”
Section: Longitudinal Functional Two-photon Imaging In Vivosupporting
confidence: 87%
“…Beginning one week later, we began imaged the calcium signals in the labeled neurons in a series of imaging sessions that continued until 16 weeks postinjection, in the awake mice viewed visual stimuli consisting of drifting gratings of different orientations and frequencies. Just as we found previously for ∆GL viruses 4,5 , cells labeled by the third-generation vector showed no signs of dysfunction for as long as we followed them (Fig. 4; see also Extended Data Figs.…”
Section: Longitudinal Functional Two-photon Imaging In Vivosupporting
confidence: 81%
See 3 more Smart Citations